DETERMINASI EFEKTIVITAS PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS): PERAN PARTISIPASI STAKEHOLDER, TRANSPARANSI, DAN AKUNTABILITAS - Khintania Salsabila Putri Shardi; Yulia Fitri (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to examine the influence of stakeholder participation, transparency, and accountability on the effectiveness of managing the School Operational Assistance (BOS) funds in junior high schools in Aceh Barat Daya Regency. The population of this research includes all 24 junior high schools, with a total sample of 96 respondents consisting of principals, treasurers, school committee members, and teachers selected through purposive sampling. Primary data were collected using a questionnaire measured on a Likert scale of 1 to 5. The data were analyzed using multiple linear regression with the assistance of SPSS. The results indicate that stakeholder participation, transparency, and accountability simultaneously have a significant effect on the effectiveness of BOS fund management. Partially, transparency and accountability have a significant effect, while stakeholder participation does not show a significant effect on the effectiveness of BOS fund management. The coefficient of determination (R²) of 0.267 indicates that 26.7% of the variation in the effectiveness of BOS fund management can be explained by the three independent variables, while the remaining percentage is influenced by other factors not examined in this study.